Enamelled mineral substrate and method for producing same
Patent Information
- Application Number
- JP2024523631
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-19
- Filing Date
- 2022-10-18
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-10-18
AI Technical Summary
【0022】 本発明の顕著な利点は、金属器具の、1つ又は複数のエナメル上への繰り返される摩擦の影響からの、目に見える金属痕及び痕跡の数の明らかな減少である。この減少は、標準的なエナメルを有するガラスセラミック基材と比較して、50%以上、又はさらには70%以上に達しうる。
Smart Images

Figure 0007634779000010 
Figure 0007634779000011 
Figure 0007634779000012
Abstract
Description
[Technical field]
[0001] The present invention relates to a mineral substrate having, on at least one of its surfaces, an inorganic enamel resistant to metallic friction. It also relates to a method for producing such a substrate. [Background technology]
[0002] Mineral substrates, such as glass-ceramics or colored specialty glasses, are popular in many fields due to their aesthetic qualities and their physical / chemical properties, in particular their low coefficient of thermal expansion and their resistance to thermal shock.
[0003] They are used in particular in kitchen fittings, especially in the form of flat substrates, for example as cooking surfaces in cooking appliances, walls of glazing ovens and as work surfaces in worktops, tables or furniture for preparing food.
[0004] As an example, in kitchen fittings, glass ceramics are mineral-based composite materials containing an amorphous phase in which crystalline phases are dispersed, which are very widely appreciated due to their very good resistance to thermal shock, their very low coefficient of expansion and their mechanical strength. As cooking surfaces and / or work surfaces in cooking equipment, they are generally based on lithium aluminosilicates in which crystalline phases based on β-quartz and / or β-spodumene are dispersed in their amorphous matrix.
[0005] Depending on the desired use of the kitchen equipment, the mineral substrates may be associated with electrical and / or electronic devices, such as heating means and / or lighting means, and / or may be provided with a number of accessories, such as controls, sensors and displays, allowing interaction between the user and the devices in which these substrates are incorporated.
[0006] It is common to enamell the surface of a mineral substrate for decorative purposes and / or to define certain functional areas, such as the control, signalling and / or heating zones of a cooking device, etc. Enamelling is typically done using screen or inkjet printing methods.
[0007] In the field of mineral substrates used in and / or near cooking equipment, for durability and aesthetic reasons, the enamel preferentially adheres well to the substrate on which it is deposited and has outstanding resistance to the mechanical and / or chemical stresses to which the enamel may be subjected under the conditions in which the cooking equipment is used.
[0008] In particular, there is a general need for enamels that can withstand repeated exposure to food and / or chemical items, and that can withstand mechanical stresses, such as metal friction, caused by repeated movement of kitchen utensils, such as pots or pans.
[0009] The prior art provides numerous examples of enamel compositions, mineral inks and / or mineral pastes, as well as examples of suitable enameling methods.
[0010] French patent application FR 2 858 974 [SCHOTT AG [DE]] 25.02.2005 describes a glass-ceramic cooking surface which is provided with a strong artificial black decorative effect that is not too rough.
[0011] WO 2016 / 008848 [SCHOTT AG [DE]] 21.01.2016 describes a mineral ink that is suitable for printing decorative effects on glass-ceramic substrates with a low coefficient of expansion, which makes it possible to obtain enamels that have a comparatively better resistance to bending and peeling.
[0012] WO 2016 / 110724 [FENZI SPA [IT]] 14.07.2016 describes a mineral ink composition for printing decorative effects on glass-ceramic substrates, which makes it possible to obtain enamels that are chemically resistant to acids, bases and radiation and mechanically resistant to abrasion and peeling.
[0013] EP 3 067 334 A1 [SCHOTT AG [DE]] 14.09.2016 describes a decorative enamel for glass-ceramic substrates which makes it possible to reduce the noise generated by the movement of kitchen utensils over the enamel surface.
[0014] WO 2019 / 219691 [EUROKERA [FR]] 21.11.2019 describes a mineral ink for printing on glass-ceramic substrates, which makes it possible to obtain an enamel that is resistant to food, to detergents, to the combined effects of repeated exposure to these articles and heating cycles, as well as to temperatures of over 800° C. used in the manufacture of glass-ceramic substrates. Summary of the Invention [Problem to be solved by the invention]
[0015] Metallic friction associated with repeated movements on mineral substrate surfaces in and / or near cooking devices, such as kitchen utensils, for example pots or pans, causes the appearance of metallic marks or marks on decorative enamel. These metallic marks or marks are generally metal particles that, under the effect of repeated friction of the metal utensil on the enamel, are detached from the metal utensil and embedded in the substrate or enamel surface. This phenomenon is particularly evident on utensils based on soft light-colored metals, such as pots or pans with aluminum or stainless steel bases.
[0016] Over time, these embedded particles can reduce the aesthetic appearance of the enamel, especially enamels that have a low contrast with the mineral substrate, such as dark or black enamel on a dark or black mineral substrate, etc. In the long term, such deterioration in aesthetics can detract from a favorable customer perception of the article.
[0017] On the other hand, with the development of so-called "flexible" cooking surfaces, i.e. surfaces where utensils may be placed in any position to heat them, or in other words where there is no dedicated heating zone, utensils are moved relatively frequently over the cooking surface, and aesthetic deterioration caused by metal friction becomes more noticeable or occurs relatively quickly.
[0018] Finally, the build-up of embedded metal particles, especially when it becomes visible, leads users to clean the glass-ceramic substrate and enamel surfaces relatively frequently and relatively vigorously. These cleanings are generally aimed at removing the visible metal marks and traces. However, the frequency and vigor of such cleaning has the negative consequence of causing early and serious damage to the enamel. This damage then reduces the aesthetic appearance of the decorative enamel and reduces the durability of the cooking surface.
[0019] Therefore, there is a need for a glass-ceramic substrate having a decorative enamel that can limit the appearance of metal marks or imperfections. [Means for solving the problem]
[0020] According to a first aspect of the present invention there is provided a mineral substrate (1001) as claimed in claim 1, the dependent claims being advantageous embodiments.
[0021] According to a second aspect of the invention, there is provided a method of manufacturing a substrate according to the first aspect of the invention. Effect of the Invention
[0022] A notable advantage of the present invention is the clear reduction in the number of visible metal marks and imprints from the repeated rubbing effects of metal instruments on one or more enamels, which can reach 50% or more, or even 70% or more, compared to glass-ceramic substrates with standard enamels.
[0023] A second advantage is that a reduction in the number of visible metal marks or imprints is observed, especially for appliances based on the most common light colored metals such as aluminum or stainless steel.
[0024] A third advantage is that the reduction in the number of visible metal marks and imprints is particularly noticeable for decorative enamels that have a low level of contrast with the mineral substrate, such as dark or black enamel on a dark or black mineral substrate.
[0025] A fourth advantage is the ease of implementation of the invention, which makes it possible to apply it to any chemical composition of enamel. [Brief description of the drawings]
[0026] [Figure 1] FIG. 1 is a schematic orthogonal view of a mineral substrate carrying enamel.
[0027] [Diagram 2] FIG. 2 is a schematic orthogonal projection of a cross section of a mineral substrate with enamel.
[0028] [Diagram 3] FIG. 3 is an example of a surface profile of an inorganic enamel on a mineral substrate according to the invention.
[0029] [Figure 4] FIG. 4 is a schematic diagram of an example of a pattern formed by an inorganic enamel in the sense of the present invention.
[0030] [Diagram 5]FIG. 5 is a first example of a 3D representation of a topographic profile in an embodiment according to the invention.
[0031] [Figure 6] FIG. 6 is a second example of a 3D representation of a topographic profile in an embodiment according to the invention.
[0032] [Figure 7] FIG. 7 is a graphical representation of total roughness as a function of topographic slope for examples according to the invention and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] In the sense of the present invention, "enamel" is understood to mean a vitreous or composite material, generally comprising annealed glass frit, in which fillers, agents and / or coloring and / or structuring pigments can optionally be dispersed.
[0034] In the sense of the present invention, a "pattern" is understood to mean a discontinuous decorative grid having, with respect to a given surface of the mineral substrate covered by said pattern, a coverage of said surface that is strictly less than 100%, preferably less than 90%.
[0035] In the sense of the present invention, the "coverage" of an enamel forming a pattern on a given surface of a mineral substrate is understood to mean the proportion of said given surface that is covered by said pattern, in other words, it corresponds to the proportion, expressed as a percentage, of the surface that is covered by the pattern on said given surface.
[0036] According to these last two definitions, a "solid" consists of a uniform, i.e. continuous, grid, for a given surface of a mineral substrate, having 100% coverage of said surface, and is not a pattern.
[0037] In the sense of the present invention, "ink coverage" means ink coverage as known and defined in the field of inkjet printing. For a given individual ink, it corresponds to the number of pixels actually printed relative to the total number of printable pixels. In the case of inkjet printing, it may depend on the accuracy of the printing device used.
[0038] In the sense of the present invention, "topographic slope" is understood to mean the current measurement of gradient, defined as the tangent of the inclination between two points of a surface located at different altitudes, or also as the tangent of the gravity angle to a reference level (generally horizontal). This measurement is generally expressed as a percentage.
[0039] In the sense of the present invention, "total roughness" is understood to mean the total roughness, denoted Rt, as defined in section 4.1.5 of the ISO 4287:1997 standard, which is defined as the sum of the maximum profile peak height Zp and the maximum profile valley depth Zv over the sampling length of the profile.
[0040] As an illustrative example, with reference to Figure 1, a mineral substrate 1001, such as one used as a surface for a cooking appliance, includes a mineral substrate 1001 which itself is provided on at least one of its surfaces with an inorganic enamel 1002. In Figure 1, the enamel 1002 is shown in the form of lines forming part of a pattern. It may form any suitable pattern.
[0041] An example of the pattern is in the form of a periodic pattern of squares, each of which is about 1.25 mm on a side, has a thickness of 1-3 μm and is spaced 0.75 mm apart. The coverage of the inorganic enamel on the surface of the substrate is 40%.
[0042] According to a first aspect of the invention, with reference to figures 1 and 2, a mineral substrate 1001 is provided, on at least one of its surfaces, with a pattern having an inorganic enamel 1002, characterized in that: - said inorganic enamel 1002 has a total roughness Rt of its surface 1002-S of less than or equal to 2 μm; and the ends 1002a, 1002b of the inorganic enamel 1002 protruding from the surface 1001-S of the mineral substrate 1001 have a topographical slope value, expressed as a percentage, of less than or equal to 1.4%.
[0043] Without limiting the invention to theoretical or practical considerations, one possible explanation for the significant advantages offered by the present invention is that the synergistic effect between a total surface roughness of less than 2 μm and a topographical slope of less than 1.4% for inorganic enamel makes it possible to improve the sliding of metal instruments, in particular soft metals, on the surface of said inorganic enamel, thus reducing the risk of metal particles being torn off.
[0044] According to the previous definition, the topographic slope corresponds to the tangent of the gradient of the ends 1002a, 1002b of the inorganic enamel 1002 which form a pattern protruding from the surface 1001-S of the mineral substrate 1001. In other words, with reference to Fig. 2, it corresponds to the tangent of the height change to the distance spanned by said height change, i.e. the ratio h / l of the height difference h between the surface 1001-S of the mineral substrate 1001 and the upper surface 1002-S of the inorganic enamel 1002, over the distance l between the two points considered for the height difference. Expressed as a percentage, the ratio h / l is multiplied by 100.
[0045] The topographic gradient of the organic enamel forming the pattern can vary according to the method and parameters of its deposition on the surface of the mineral substrate, depending on the thickness of said organic enamel, its chemical composition and / or the particle size of the mixture that has been used to form it, such as the particle size of the mixture of mineral glass frits and / or mineral pigments (inorganic pigments), especially in combination. However, these characteristics are not sufficient alone to define a given topographic gradient value. In other words, two inorganic enamels of the same composition, obtained with the same mixture and having the same thickness, can have different topographic gradients depending on the method by which they are deposited on the mineral substrate.
[0046] The upper surface 1002-S of the inorganic enamel 1002 is generally the largest surface and is substantially parallel to the surface 1001-S of the mineral substrate 1001.
[0047] The slope angle, expressed in radians, is the angular expression of the topographic slope. The slope angle α is then expressed as the arctangent or tangent of the ratio h / l. -1 This corresponds to the value obtained by applying the inverse tangent function, denoted as
[0048]
number
[0049] This ratio can be multiplied by 180 / π to convert the angle into degrees.
[0050] The value of the topographic slope is preferably the arithmetic mean of the individual topographic slope values measured at different locations or in different positions of the ends 1002a, 1002b of the inorganic enamel 1002 protruding above the surface 1001-S of the mineral substrate 1001.
[0051] Pattern-forming enamels generally have the function of being decorative and / or functional coatings deposited on the surface of mineral substrates for decorative, marking and / or definition purposes, in particular for defining specific functional areas, such as the heating and / or control areas of a cooking appliance or worktop.
[0052] Various enamelling processes, also called glazing or more simply decorative, and the compositions of mineral or ceramic pastes, inks or paints used for the purposes of said enamelling processes are known from the prior art, in particular in the field of enamels on mineral substrates, such as glass-ceramics.
[0053] The enamels are generally obtained by thermal treatment of pastes, inks or mineral or ceramic paints that are deposited on the surface of the mineral substrate using a suitable method, such as screen printing or inkjet printing.
[0054] A paste, ink, or mineral or ceramic paint comprises a solid mineral phase (solid inorganic phase) finely divided and dispersed in a more or less viscous organic medium, which allows the solid phase to be applied in a suitable deposition manner, and which has the function of suspending and / or dispersing the mineral phase (inorganic phase), thereby ensuring its uniform and homogeneous distribution in the decorative, marking and / or defined areas.
[0055] The mineral substrate 1001 may be any mineral substrate capable of undergoing stress by metal utensils, and in particular may be a mineral substrate capable of being used in an environment in which kitchen utensils are used, for example as a worktop surface and / or an appliance surface and / or a cooking unit surface.
[0056] In some embodiments, the mineral substrate 1001 can be a glass-ceramic substrate or a mineral glass substrate. By way of example, it can be any type of glass-ceramic, such as a glass-ceramic based on lithium aluminosilicate, suitable for use as a worktop surface and / or a surface of an appliance and / or a surface of a cooking unit. It can also be any type of mineral glass, optionally reinforced, suitable for similar applications, such as a borosilicate glass or an aluminosilicate glass.
[0057] According to the invention, the total surface roughness value of the inorganic enamel 1002 is less than or equal to 2 μm. For certain inorganic enamel compositions, relatively low total roughness values can be reached. Thus, in certain advantageous embodiments, said total surface roughness value can be less than or equal to 1.5 μm, preferably less than or equal to 1 μm. It has been observed that a reduction in the total surface roughness can further reduce the visibility of metal marks and traces.
[0058] According to the invention, the topographical slope value of the ends 1002a, 1002b of the inorganic enamel 1002 protruding at the surface 1001-S of the glass-ceramic substrate 1001 is less than or equal to 1.4%. For certain inorganic enamel compositions 1002, relatively low values can be reached. Thus, in certain advantageous embodiments, said topographical slope value can be less than or equal to 1.2%. It has been observed that a reduction in the topographical slope can further facilitate the sliding of metal objects or instruments on the inorganic enamel and thus make it possible to further reduce the visibility of metal marks and traces.
[0059] The reduced visibility of metal marks and traces made possible by the present invention allows the thickness of the inorganic enamel to be advantageously reduced, since the need to compensate for possible damage to the enamel caused by embedding of metal particles and / or repeated cleaning by the user becomes less critical or even non-existent.
[0060] Thus, in certain embodiments, the thickness of the inorganic enamel 1002 may advantageously be between 1.5 μm and 3.5 μm, or even between 1.5 μm and 2 μm.
[0061] Metal marks and traces are significantly reduced for inorganic enamel 1002, which has a low level of contrast with the mineral substrate 1001, even if the mineral substrate 1001 has a dark appearance, in particular a black appearance, or a light-colored appearance, for example a white appearance. Thus, in a particularly advantageous embodiment, the relative luminance difference ΔL * is the luminance L, measured in reflection, of an inorganic enamel 1002 on a mineral substrate 1001 * Luminance L, measured in reflection, of the mineral substrate 1001 without the inorganic enamel 1002 (enamel / substrate) and of the mineral substrate 1001 without the inorganic enamel 1002 * (substrate) and is at most 50, preferably at most 35. It may in particular be between 2 and 45, optionally between 5 and 35, these values corresponding to a rather low contrast inorganic enamel 1002 with respect to the mineral substrate 1001.
[0062] In addition, the relative luminance difference ΔL * can be expressed in the form of the following formula:
[0063]
number
[0064] The term "luminance" refers to the luminance, L, defined and measured in the ISO 11664-4 standard. * It is written as , and is understood to mean luminance. * The luminance of the mineral substrate 1001, denoted as (substrate), is measured in reflection. The luminance of the inorganic enamel 1002 deposited on the mineral substrate 1001 is measured in reflection, L * (enamel / substrate) and is measured in reflectance.
[0065] In cooking appliances or worktops, the mineral substrate with which the inorganic enamel has a low contrast difference is generally a substrate with a dark appearance, optionally black, weakly transparent and low scattering. Also, in certain embodiments, the light transmittance Tl of the mineral substrate 1001 is at most 17%, preferably 10% or less, or even 5% or less. Black mineral substrates, such as non-opaque standard black glass ceramics, have a light transmittance of less than 5%, in particular 0.2% to 2%.
[0066] "Light transmittance" is understood to mean the light transmission, denoted Tl, as defined and measured in section 4.2 of standard EN 410:1999, using illuminance D65 and a standard observer.
[0067] In a particular embodiment, the luminance L of the mineral black substrate, measured in reflection of the mineral substrate 1001, * The (substrate) may even be less than or equal to 5, preferably less than or equal to 2. Black mineral substrates, such as the glass-ceramics sold under the names KeraBlack® or KeraBlack+® by the company Eurokera, have such brightness levels.
[0068] One advantage of the present invention is that it promotes the sliding of metal instruments, especially those of soft metals, over the surface of the inorganic enamel, thus reducing the risk of metal particles being torn off.
[0069] In an advantageous embodiment, the coefficient of friction, also called the static and / or kinetic coefficient of friction, of the surface of the mineral substrate (1001) with said inorganic enamel (1002) is at most 0.30, preferably at most 0.25. Mineral substrates according to the invention with such values of the static and / or kinetic coefficient of friction generally have the best performance in terms of reducing the number of visible metal marks and traces from the effects of repeated rubbing of metal instruments.
[0070] Coefficient of friction is understood to mean the static and / or kinetic coefficient of friction as defined in the standards ASTM D1894, ISO 8295:1995 and ISO 15359:1999.
[0071] The coefficient of static friction is defined as the ratio between the static friction force, i.e., the force required to initiate a sliding motion of one surface over another, and the force applied normal to these two surfaces to maintain their contact and sliding.
[0072] The coefficient of kinetic friction is defined as the ratio between the kinetic frictional force, i.e., the force required to maintain a sliding motion of one surface over another, and the force applied perpendicularly to these two surfaces to maintain their contact and sliding.
[0073] The static and / or kinetic coefficient of friction of the surface of the mineral substrate (1001) on which the inorganic enamel (1002) is provided is understood to mean the static and / or kinetic coefficient of friction that can be measured on the surface of the mineral substrate (1001) on which the inorganic enamel (1002) is present.
[0074] The mineral substrate 1001 according to any of the described embodiments may be advantageously used as a surface for a cooking appliance, in particular an induction cooking appliance having a so-called "flexible" surface, or as a surface for a worktop, in particular a worktop surface in furniture fittings such as a food preparation table or a work cabinet.
[0075] According to a second aspect of the present invention, there is provided a method for producing a mineral substrate 1001 according to any one of the previously described embodiments, said method comprising a step of depositing an inorganic enamel 1002 by inkjet printing a mineral ink onto the mineral substrate 1001, wherein the ink coverage is at least 45% and at most 85%, and the weight percentage of solids in the mineral ink used for inkjet printing is at most 40% of said mineral ink.
[0076] As an illustrative example, for an inkjet printing task at 800 dpi, the number of printable pixels on a 1 inch square pattern is 640,000 pixels. If only 200,000 pixels are actually printed for a given individual ink, then the ink coverage for that given individual ink is 200,000 / 640,000, or expressed as a percentage, 31.5%.
[0077] When multiple individual inks are used, for example inks of different colors, the ink coverage is the sum of the ink coverage of each of these individual inks.
[0078] The viscosity of the ink, typically between 20 and 100 Pa·s, and the volume of the ink droplets, typically between 12 and 84 pL, can also affect the ink coverage. Very fluid inks and / or large drop volumes can result in relatively large coverage of the printing surface, especially by covering pixels surrounding the pixels actually printed by the inkjet printing device at the selected resolution. These parameters are generally taken into account by the inkjet printing device when defining the ink coverage.
[0079] "Mineral ink" is understood to mean a mineral ink suitable for depositing an enamel by inkjet printing. Mineral inks are generally in the form of a suspension or colloidal dispersion of a finely divided solid mineral phase, generally in an organic liquid phase. The solid mineral phase of the colloidal suspension generally comprises a glass frit and, optionally, a mineral pigment.
[0080] Mineral inks have a density, viscosity and surface tension that are compatible with the inkjet printing process. The values of these parameters depend on the inkjet printing device used and affect the quality of the decorative pattern obtained.
[0081] The size of the grains constituting the solid mineral phase is typically micrometer or even submicrometer. The liquid phase mainly comprises a solvent, typically an organic solvent. The type and amount of the solvent partially influences the rheological properties, the surface tension and the drying behavior of the mineral ink. Dispersants may be added to prevent aggregation and / or settling of the solid phase, and surfactants may be added to adjust the surface tension of the mineral ink.
[0082] The weight ratios of organic solvent, dispersant, surfactant and glass frit can be adjusted to match the properties of the mineral ink to the equipment used for inkjet printing. The organic solvent may typically represent 80% by weight of the mixture of organic solvent, dispersant and surfactant of the mineral ink. The type and amount of organic solvent can be adjusted according to the technical and production constraints of the inkjet printing equipment used.
[0083] To form an enamel using mineral ink deposited by inkjet printing, the temperature for drying the mineral ink can be 25-180° C. The temperature for the firing heat treatment of the enameled precursor glass can be 650° C. or higher. Preferably, the temperature does not exceed 1100° C.
[0084] The organic solvent can be an organic compound that is liquid at room temperature or a mixture of organic compounds that are liquid at room temperature and that contain at least one alcohol functional group.
[0085] The choice of organic compound containing alcohol functional groups depends on the method and / or device used for inkjet printing. If the deposition of the mineral ink on the mineral substrate is slow, it is advantageous to use a solvent or mixture of solvents that has a low saturated vapor pressure under the applied pressure and temperature conditions of the method and / or device. In other words, the boiling point of the solvent or mixture of solvents can be high to prevent it from evaporating too quickly under standard temperature and pressure conditions.
[0086] Non-limiting examples of organic solvents include: methylene glycol, ethylene glycol, propylene glycol, butylene glycol, methanol, ethanol, propanol, butanol, glycol ethers such as propylene glycol methyl ether or dipropylene glycol methyl ether.
[0087] The dispersant is preferably a copolymer or a mixture of copolymers containing at least one acid functional group. The dispersant makes it possible to prevent aggregation and / or sedimentation of the solid phase. It preferably represents 3-7% by weight, and at most 10% by weight, of the total mass percentage of the organic solvent, the dispersant and the surfactant. Alkylammonium salts of copolymers containing one or more acid functional groups are non-limiting examples of dispersants.
[0088] The surfactant is preferably a polyether or a mixture of polyethers, which preferably represents 0.05% to 0.5% by weight of the total mass percentage of the organic solvent, the dispersant and the surfactant.
[0089] The mineral ink may not include colored mineral pigments. Alternatively, it may include mineral pigments to provide a shade or color to the enamel. The mineral pigments make it possible to adjust the color of the mineral ink and the enamel. The mineral pigments may be based on metal oxides and / or metals or metal alloys that can be oxidized during heat treatment of the mineral ink to form the enamel. Non-limiting examples of mineral pigments are titanium oxide, cerium oxide, cobalt oxide, iron oxide, zirconium oxide, manganese oxide, spinel, or doped alumina.
[0090] In one embodiment, the particle size distribution of the solid fraction of the mineral ink has a D90 of at most 2 μm, preferably between 1 μm and 2 μm. D90 is calculated from the particle size distribution determined by laser diffraction according to the ISO 13320:2009 standard. This corresponds to the size of the particles that represent 90% of the total particle volume of the mixture. In other words, 90% of the particle volume of the mixture of glass frit and mineral pigment consists of particles with a size of at most 2 μm, preferably between 1 and 2 μm. In an advantageous embodiment, the surface tension of the mineral ink is about 26 mN / m at 25° C. It has been found that a mineral ink having a surface tension of about 26 mN / m at 25° C. can facilitate obtaining an inorganic enamel on a mineral substrate according to the first aspect of the invention.
[0091] All described embodiments, whether they relate to the first or second aspect of the invention, can be combined with each other. EXAMPLES
[0092] In the four examples E1, E2, E3 and E4 of mineral substrates according to the invention, three different inorganic enamels A, B and C are deposited on a glass-ceramic plate KeraBlack+™ (KB+) sold by the company Eurokera SNC.
[0093] Enamel A is a black enamel containing 60-70% of glass frit F of the composition set out in Table 1, 15-20% mixed oxides of cobalt and silicon, and 15-20% mixed oxides of iron, chromium, cobalt, and nickel.
[0094] Enamel B is a dark grey enamel formed from a mixture of 75% by weight of enamel A and 25% by weight of enamel containing 70-75% by weight of glass frit F of the composition set out in Table 1 and 25-30% by weight of titanium oxide.
[0095] Enamel C is a grey enamel formed from a mixture of 50% by weight of enamel A, 70-75% by weight of glass frit F of the composition set out in Table 1 and 25-30% by weight of titanium oxide.
[0096] [Table 1]
[0097] In examples E1, E2 and E3, the inorganic enamels were produced according to the method according to the second aspect of the invention, more particularly by inkjet printing of a mineral ink with an ink coverage Te of 55%. The solids content in the mineral ink is up to 40% by weight. The particle size distribution D90 of the solids content of the mineral ink is about 1.3-1.5 μm.
[0098] In Example E4, the inorganic enamel was deposited by a non-standard screen printing method using a screen printing paste with a solid fraction particle size distribution D90 of about 1.6 μm.
[0099] In a first comparative example CE1 not according to the invention, the inorganic enamel A is deposited by standard screen printing methods on a glass-ceramic plate known as KeraBlack+™ (KB+) sold by Eurokera SNC The particle size distribution D90 of the solid fraction of the screen printing paste is about 5.1 μm.
[0100] In a second comparative example CE2 not according to the invention, the inorganic enamel A is deposited by printing a mineral ink on a glass-ceramic plate known as KeraBlack+™ (KB+) sold by Eurokera SNC, with an ink coverage Te of 40%. The particle size distribution of the solid fraction of the mineral ink has a D90 of about 1.4 μm.
[0101] In Examples E1, E4 and Comparative Example CE1, the enamel is deposited in the form of a periodic pattern with a square shape of about 1.25 mm on a side, a thickness of 1-3 μm, and a spacing of 0.75 mm, as shown diagrammatically in FIG. 4.
[0102] In Examples E2, E3 and Comparative Example CE2, the enamel is deposited in the form of random units and the coverage of the enamel on the substrate is about 25%.
[0103] The characteristics of Examples E1, E2, E3 and E4, and Comparative Examples CE1 and CE2 are summarized in Table 2.
[0104] [Table 2]
[0105] The light transmission of the mineral substrate alone, i.e. without inorganic enamel, was measured using a Perkin Elmer Lambda 950 spectrophotometer, with illuminance D65 and a standard observer, according to section 4.2 of the EN 410:1999 standard. For the examples E1, E2, E3 and E4, and for the comparative examples CE1 and CE2, the light transmission Tl measured on the mineral substrate alone is about 1.5%.
[0106] Brightness, L * and was measured using a BYK Gardner SPC008 spectrophotometer at an illumination angle of 45° and an observation angle of 0° according to the ISO 11664-4 standard.
[0107] The luminance of the mineral substrate alone, i.e., without inorganic enamel, is * (substrate) on a white background, in this case the standard background chart 2810 (L) supplied by BYK Gardner. * = 92.07, a * =-0.75, b * =4.91) and measured in reflection.
[0108] The brightness of inorganic enamel deposited on a mineral substrate is defined as L *It is expressed as (enamel / substrate) and is measured in reflectance. The surface of a mineral substrate is completely covered by inorganic enamel.
[0109] Relative luminance difference ΔL * is calculated using the following formula:
[0110]
number
[0111] The total surface roughness Rt of each of the inorganic enamels of Examples E1, E2, E3 and E4 and Counterexamples CE1 and CE2 was measured using a Mitutoyo SJ-400 mechanical probe according to section 4.1.5 of ISO standard 4287:1997.
[0112] The topographic slope Pt of the inorganic enamel protruding from the surface of the glass-ceramic substrate is calculated using the surface profile, which is measured using a Mitutoyo SJ-400 mechanical probe with a PC75 (non-Gaussian) filter applied to the parameter Wt.
[0113] An illustrative example of a surface profile measurement on an inorganic enamel on a mineral substrate surface according to the present invention is shown in FIG.
[0114] The profile is measured over a length of 15 mm on the edge of the enamel protruding onto the surface of the mineral substrate. The enamel has a polygonal geometric shape. The topographic slope, which corresponds to the tangent of the height change between the surface of the mineral substrate and the so-called effective surface of the enamel, is calculated using the following formula:
[0115]
number
[0116] where h is the height difference between the surface of the mineral substrate and the effective surface of the inorganic enamel, generally corresponding to the thickness of the enamel relative to the surface of the mineral substrate, and l is the length spanned by the height change.
[0117] At least three measurements of the topographic slope are carried out on the same inorganic enamel at different locations or at different positions of the edge of the enamel protruding from the surface of the mineral substrate. The arithmetic mean value Ptm of the topographic slope is calculated from these at least three measurements.
[0118] 5 and 6 are examples of 3D representations of topographic profiles, measured using a Taylor Hobson 3D surface profilometer from AMETEK in an embodiment according to the invention, from which surface profile measurements may be made.
[0119] The visibility of metal friction was evaluated using the following protocol: a pot made of stainless steel or aluminum, with a diameter of 20 cm and weighing 3 kg, is placed at an angle on a mineral substrate provided with an inorganic enamel and moved in 10 double movements at a speed of about 0.40 m / s. The stainless steel pot has a Vickers hardness of 200 HV.
[0120] The level of metallic rub marks is assessed according to two different methods: visual analysis and image analysis.
[0121] According to the first visual analytical evaluation method, the degree of deterioration D of the enamel is visually evaluated under normal observation conditions at a distance of 60 cm according to a scale of 0 to 5. A degree of 5 corresponds to a noticeable visibility of the embedded metal particles, a degree of 0 corresponds to no visible metal marks or traces. In other words, the lower the degree, the less visible the metallic friction marks or traces are to the naked eye.
[0122] According to the second image analysis evaluation method, firstly a digital photographic image is taken of a defined area of the enamel under artificial light of three-color light-emitting diodes in a light box suitable for this purpose.
[0123] The digital photographic image is then subjected to digital processing to convert it into a grey-scale image, from which the average grey level value Vm is calculated.
[0124] This same operation is carried out for an area of enamel that has been subjected to metallic friction and for an area of enamel that has not been subjected to metallic friction. The difference ΔVm between the values Vm obtained for each of these two areas is calculated. The greater the value of the parameter ΔVm, the greater the number of metal particles embedded in the enamel.
[0125] In parallel, the same photographic image is subjected to a digital binarization process from which a visibility index Iv is calculated, defined as the ratio of the number of pixels with a relatively high intensity, i.e. the number of pixels with the value 1, to the total number of pixels. The higher this ratio Iv is, the higher the visibility of the metal particles embedded in the enamel.
[0126] The image size is 3264x2448 pixels, with respect to the size of the enamel analysis zone consisting of 400,000 to 450,000 pixels, which corresponds to about 10x13 squares of the pattern for Examples E1, E4 and Comparative Example CE1.
[0127] The static and kinetic coefficients of friction, designated Fs and Fd, respectively, were measured on an AFT device for measuring the coefficient of friction, sold by Hanatek Instruments™, according to the standards ASTM D1894, ISO 8295:1995 and ISO 15359:1999. The friction head is a stainless steel washer of type NFE25.513 from Berner®, with a diameter of 36 mm and a thickness of 2 mm. The measurements were carried out with a friction head travel speed of 500 mm / min over a stroke of 50 mm.
[0128] Before measuring the coefficient of friction, the samples are pre-cleaned with Clin'Glass detergent sold by Laboratoires Prodene Klint.RTM. Four measurements are carried out for each sample and their average value is calculated.
[0129] For these measurements, the inorganic enamel on the substrate surface has a random pattern for Examples E2 and E3 and Comparative Example CE2, and a periodic pattern of squares measuring approximately 1.25 mm on a side for Examples E1, E4 and Comparative Example CE1.
[0130] All results are summarized in Table 3. Values of parameters D, ΔVm and Iv are reported for metallic friction with stainless steel (stainless) and aluminium (alu) pots and are annotated as "stainless" and "alu", respectively. [Table 3]
[0131] The results in Table 3 show that the number of metal marks and marks, and therefore their visibility, is reduced for the examples E1, E2, E3 and E4 according to the invention compared to the comparative examples CE1 and CE2. In fact, whether the parameters D, ΔVm and Iv, which take into account the friction with stainless steel or aluminum pots, their values are lower for the examples according to the invention. The values of the parameters ΔVm and Iv are reduced by 75% to 92%, which means that the visibility of metal marks and marks is reduced as much as possible.
[0132] Comparison of the results of Example E1 and Example E4 shows that the parameter values D, ΔVm and Iv are relatively low when the manufacturing method according to the second aspect of the present invention is used.The manufacturing method according to the present invention therefore allows to obtain a better performance than the screen printing method in terms of reducing the visibility of metallic marks and marks.The use of the screen printing method is still possible.
[0133] Comparison of the results of Examples E1, E2 and E3 shows that the visibility of metal marks and traces is significantly improved in inorganic enamels with a low level of contrast with the mineral substrate, particularly in ΔL * Dark appearance with ΔL less than 35, especially * It can be seen that even for inorganic enamels, which are black in colour with a colour of less than 15, the colour remains very reduced.
[0134] As a further illustration of the features and advantages of the present invention, some examples taken from the prior art are reproduced in comparative form and their characteristics are reported in Table 4.
[0135] [Table 4]
[0136] Comparative examples CE3 to CE8 are taken from EP 3 067 334 A1 [SCHOTT AG [DE]] 14.09.2016. Examples CE3 to CE5 on the one hand and comparative examples CE6 to CE8 on the other hand each have three different enamel compositions (Farbe(color) 1, Farbe(color) 1a and Farbe(color) 6). These two series of comparative examples are deposited according to two different patterns (Punktmuster(polka dot) 11 and Punktmuster(polka dot) 12).
[0137] Comparative examples CE7 and CE9 have the same enamel composition as taken from FR 2 858 974 [SCHOTT AG [DE]] 25.02.2005. For comparison purposes, they are deposited according to two different units (Punktmuster (polka dots) 11 and Punktmuster (polka dots) 12) as taken from EP 3 067 334 [SCHOTT AG [DE]] 14.09.2016.
[0138] Comparative Examples CE11 and CE12 present the compositions of Examples E1 and E2, respectively, of WO 2019 / 219691 [EUROKERA [FR]] 21.11.2019. For comparison purposes, they are deposited according to a line pattern with a width of 0.6 mm at a coverage of 55%.
[0139] The enamels of comparative examples CE3 to CE12 may have the same chemical composition and / or particle size of the mixtures used to form them as examples E1 to E4 according to the invention, such as mixtures of mineral glass frits and / or mineral pigments.
[0140] The enamels of Examples CE3 to CE8 were deposited according to the methods described in the literature from which they were extracted.
[0141] The total roughness and topographic slope of Comparative Examples CE1-CE3 were measured and / or determined according to the same methods used for Examples E1-E4 and Comparative Examples CE1 and CE2, and the results are reported in Table 5 and shown in FIG.
[0142] [Table 5]
[0143] 7, Examples E1-E4 according to the invention are represented by solid circle symbols, Comparative Examples CE3-CE5 by open diamonds, Comparative Examples CE6-CE8 by stars, Comparative Examples CE9-CE10 by open squares, and Comparative Examples CE11 and CE12 by open triangles. As a visual guide, the total roughness value Rt at 2.00 μm and the topographic slope Ptm at 1.40% are represented by dashed vertical and dashed horizontal lines, respectively.
[0144] 7 shows that only the examples according to the invention are located within the zone defined below the horizontal line and to the right of the vertical line. Comparative Examples CE3 to CE12 are all outside this zone. Thus, this figure clearly and unambiguously shows that only the examples according to the invention have a total roughness Rt and a topographical slope value Ptm of 2.00 μm or less and 1.4% or less, respectively. The present disclosure includes the following inventive aspects: <Aspect 1> A mineral substrate (1001) having on at least one of its surfaces an inorganic enamel (1002) forming a pattern: - said inorganic enamel (1002) has a total roughness Rt of its surface (1002-S) of less than or equal to 2 μm, and - the edges (1002a, 1002b) of said inorganic enamel (1002) protruding from the surface (1001-S) of said mineral substrate (1001) have a topographical slope value, expressed as a percentage, of less than or equal to 1.4%; A mineral base material (1001). <Aspect 2> The mineral substrate (1001) according to embodiment 1, wherein the total surface roughness value is 1.5 μm or less, preferably 1 μm or less. <Aspect 3> The mineral substrate (1001) of any one of the preceding claims, wherein the topographic slope value is 1.2% or less. <Aspect 4> 4. The mineral substrate (1001) according to any one of aspects 1 to 3, wherein the inorganic enamel (1002) has a thickness of 1.5 μm to 3.5 μm, or 1.5 μm to 2 μm. <Aspect 5> A mineral substrate (1001) according to any of aspects 1 to 4, wherein the relative luminance difference ΔL*, defined as the difference between the luminance L*(enamel / substrate), measured in reflection, of the inorganic enamel (1002) on the mineral substrate (1001), and the luminance L*(substrate), measured in reflection, of the mineral substrate (1001) without the inorganic enamel (1002), is at most 50, preferably at most 35. <Aspect 6> 6. The mineral substrate (1001) according to any one of the preceding aspects, wherein the mineral substrate has a luminance L*(substrate), measured in transmission, of 5 or less. <Aspect 7> A mineral substrate (1001) according to any of the first to sixth aspects, wherein the light transmittance of the mineral substrate is at most 17%, preferably at most 10%, or at most 5%. <Aspect 8> The mineral substrate (1001) according to any of the preceding aspects 1 to 7, wherein the surface of the mineral substrate (1001) on which the inorganic enamel (1002) is provided has a static and / or dynamic coefficient of friction of at most 0.30, preferably at most 0.25. <Aspect 9> 9. The mineral substrate according to any one of aspects 1 to 8, wherein the mineral substrate is a glass-ceramic substrate or a mineral glass substrate. <Aspect 10> A method for producing a mineral substrate (1001) according to any one of aspects 1 to 9, the method comprising a step of depositing an inorganic enamel (1002) on the mineral substrate (1001) by inkjet printing a mineral ink, wherein the ink coverage is at least 45% and at most 85%, and the weight percentage of solids in the mineral ink used for the inkjet printing is at most 40% of the mineral ink. <Aspect 11> 11. The method of claim 10, wherein the mineral ink has a surface tension of about 26 mN / m at 25° C. <Aspect 12> 10. Use of the mineral substrate (1001) according to any one of the first to ninth aspects as a surface for a cooking device or a worktop.
Claims
1. A mineral substrate (1001) having on at least one of its surfaces an inorganic enamel (1002) forming a pattern: said inorganic enamel (1002) has a total roughness Rt of its surface (1002-S) less than or equal to 2 μm, and the edges (1002a, 1002b) of said inorganic enamel (1002) protruding from the surface (1001-S) of said mineral substrate (1001) have a topographical slope value, expressed as a percentage, of less than or equal to 1.4%; A mineral substrate (1001).
2. 2. The mineral substrate (1001) according to claim 1, wherein the value of the total roughness Rt is less than or equal to 1.5 μm, preferably less than or equal to 1 μm.
3. The mineral substrate (1001) according to claim 1 or 2, wherein the topographic slope value is less than or equal to 1.2%.
4. The mineral substrate (1001) according to claim 1 or 2, wherein the inorganic enamel (1002) has a thickness of between 1.5 μm and 3.5 μm, or between 1.5 μm and 2 μm.
5. 3. The mineral substrate (1001) according to claim 1 or 2, wherein the relative luminance difference ΔL*, defined as the difference between the luminance L* (enamel / substrate), measured in reflection, of the inorganic enamel (1002) on the mineral substrate (1001), and the luminance L* (substrate), measured in reflection, of the mineral substrate (1001) without the inorganic enamel (1002), is at most 50, preferably at most 35.
6. 3. The mineral substrate (1001) according to claim 1 or 2, wherein the mineral substrate has a luminance L*(substrate), measured in transmission, of 5 or less.
7. 3. The mineral substrate (1001) according to claim 1 or 2, wherein the light transmittance of the mineral substrate is at most 17%, preferably at most 10% or at most 5%.
8. The mineral substrate (1001) according to claim 1 or 2, wherein the surface of the mineral substrate (1001) on which the inorganic enamel (1002) is provided has a static and / or dynamic coefficient of friction of at most 0.30, preferably at most 0.
25.
9. 3. The mineral substrate according to claim 1 or 2, wherein the mineral substrate is a glass-ceramic substrate or a mineral glass substrate.
10. A method for manufacturing a mineral substrate (1001) according to claim 1 or 2, the method comprising a step of depositing an inorganic enamel (1002) on the mineral substrate (1001) by inkjet printing a mineral ink, the ink coverage being at least 45% and at most 85%, and the weight percentage of solids in the mineral ink used for the inkjet printing being at most 40% of the mineral ink.
11. The method of claim 10, wherein the mineral ink has a surface tension of 26 mN / m at 25°C.
12. 3. Use of a mineral substrate (1001) according to claim 1 or 2 as a surface for a cooking device or a worktop.
Citation Information
Patent Citations
Glass ceramic panel with pleasing black decoration applied with decorative paint
JP2005097097A
Glass or crystallized glass substrate coated with layer having tactile properties
JP2013082615A
Substrate coated with noise-optimized glass-based coating and method of producing such coating
JP2016169146A
Manufacturing method of glass or glass ceramic product containing coloring glass-based coating, coated glass or glass ceramic product and use thereof
JP2016169147A
Glass-ceramic articles
JP2021513947A